Kegiatan Pengukuran Tekanan Darah dan Penyakit Darah Tinggi pada Populasi Usia Produktif - Erick Sidarta; Bryan Anna Wijaya; Fiona Valencia Setiawan; Edwin Destra; Junius Kurniawan (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Hypertension is an increasing global health problem. By 2025, it is estimated that 1.5 billion people will suffer from hypertension, with 10.44 million deaths annually caused by hypertension and its complications. Most cases are idiopathic, related to genetic factors, diet and lifestyle. Uncontrolled hypertension significantly increases the risk of cardiovascular disease, kidney failure, and stroke. This activity uses the PDCA (Plan-Do-Check-Act) method for blood pressure screening and counseling in adults at PT. Narindo, North Jakarta. The results of blood pressure examination showed that 4 people (3.08%) had grade 3 hypertension, 7 people (5.38%) had grade 2 hypertension, 20 people (15.38%) had grade 1 hypertension. Monitor blood pressure regularly and increasing public health knowledge can increase awareness and encourage healthy lifestyle changes, reducing the prevalence and complications of hypertension.